Evaluating traditional Chinese medicine diagnostic instruments for functional dyspepsia: A systematic review on measurement properties - Leonard TF Ho; Vincent CH Chung; Charlene HL Wong; Irene XY Wu; Kun Chan Lan; Darong Wu; Jerry WF Yeung; Nevin L Zhang; Ting Hung Leung; Justin CY Wu (Integrative Medicine Research)
Background: Pattern diagnosis-guided treatments in Traditional Chinese Medicine (TCM) has been recognised by the eleventh revision of the International Classification of Diseases (ICD-11). Accurate pattern diagnosis requires reliable and valid diagnostic instruments that guide the collection of TCM clinical data without bias. This study synthesised the existing TCM diagnostic instruments for functional dyspepsia (FD) and appraised their quality regarding their development process and measurement properties. Methods: Seven electronic databases were searched for validation studies on TCM diagnostic instruments for FD. Synthesis and appraisal of the included studies were performed following the COSMIN (COnsensus-based Standards for the selection of health Measurement INstruments) Initiative guidelines adapted for TCM diagnostic instruments. Risk of bias assessment was conducted using the COSMIN Risk of Bias Checklist. Results: Five studies were included, with five unique TCM diagnostic instruments for FD identified. All five diagnostic instruments were of inadequate quality in terms of their development process, implying a shortcoming in their relevance, comprehensibility, and comprehensiveness. Only the criterion validity of Stomach Qi Deficiency Pattern Assessment Scale was of sufficient quality and had no risk of bias in its validation. Conclusion: The quality of TCM diagnostic instruments for FD warrants urgent improvements. None of them was considered reliable or valid for guiding TCM pattern diagnosis. To support the evidence base of the standardization of TCM patterns in ICD-11, TCM diagnostic instruments should be developed and validated rigorously under the COSMIN guidelines. Amendments should be made on the guidelines to accommodate the features and uniqueness of TCM diagnostic process.